2013
DOI: 10.1523/jneurosci.0545-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Inositol Trisphosphate Receptor Regulates Cerebellar Circuits by Maintaining the Spine Morphology of Purkinje Cells in Adult Mice

Abstract: The structural maintenance of neural circuits is critical for higher brain functions in adulthood. Although several molecules have been identified as regulators for spine maintenance in hippocampal and cortical neurons, it is poorly understood how Purkinje cell (PC) spines are maintained in the mature cerebellum. Here we show that the calcium channel type 1 inositol trisphosphate receptor (IP 3 R1) in PCs plays a crucial role in controlling the maintenance of parallel fiber (PF)-PC synaptic circuits in the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 65 publications
0
72
0
Order By: Relevance
“…Behavioral experiments revealed that IP 3 Rs are involved in memory formation; in particular, they are required for long-term memory [47]. Recently, Mikoshiba's research group has shown that the IP 3 R1 in cerebellar PCs plays a crucial role in controlling the maintenance of parallel fiber-PC synaptic circuits in the mature cerebellum in vivo [48]. Also, it has been shown that IP 3 R1, together with other important intracellular proteins, plays a significant role in PC dendritic development [49].…”
Section: Structure Function and Regulation Of Ip 3 Rsmentioning
confidence: 99%
“…Behavioral experiments revealed that IP 3 Rs are involved in memory formation; in particular, they are required for long-term memory [47]. Recently, Mikoshiba's research group has shown that the IP 3 R1 in cerebellar PCs plays a crucial role in controlling the maintenance of parallel fiber-PC synaptic circuits in the mature cerebellum in vivo [48]. Also, it has been shown that IP 3 R1, together with other important intracellular proteins, plays a significant role in PC dendritic development [49].…”
Section: Structure Function and Regulation Of Ip 3 Rsmentioning
confidence: 99%
“…However, this modification subsequently would have a chronically negative effect on Ca 2+ signaling, because it is much more static than noncovalent allosteric modulators required for the control of rapid and dynamic Ca 2+ signaling such as Ca 2+ oscillation. Therefore, the TG2-dependent allosteric modulation should chronically set in motion cascades of defective signaling related to pathological states; up-regulation of TG2 may disrupt the IP 3 R1-mediated plasticity of neuronal signaling (3,(10)(11)(12) and the homeostatic control of cellular processes including mitochondria energy production (23), autophagy regulation (24-27), ER stress (28), and others (29)(30)(31) and ultimately increases cellular stress, resulting in further TG2 up-regulation proceeding a vicious cycle. Given the widespread brain expression profiles of TG2 and IP 3 R1, we propose that the mechanism described in this study might potentially serve as a general principle for many other diseases of the brain or other tissues in which TG2 is up-regulated by a disease-initiating agent.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the genes encoding the type 1 IP 3 R (IP 3 R1) leads to perturbations in long-term potentiation/ depression (3,10,11) and spinogenesis (12), and the human genetic disease spinocerebellar ataxia 15 is caused by haploinsufficiency of the IP 3 R1 gene (13)(14)(15). Dysregulation of IP 3 R1 is also implicated in neurodegenerative diseases including Huntington disease (HD) (16)(17)(18)) and Alzheimer's disease (AD) (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Images of the same widow were taken 3, 6, and 10 days after the surgery. the deep cerebellar nuclei, and the structural plasticity of Purkinje cell spines has been of great interest (Black et al 1990;Cesa et al 2005Cesa et al , 2007Kleim et al 1998;Lee et al 2007Lee et al , 2013Sdrulla and Linden 2007;Sugawara et al 2013). However, because of the small size and high density of spines, single spines are not reliably resolved in vivo even with two-photon microscopy.…”
Section: Discussionmentioning
confidence: 99%